Social Tariqah and Nusantara Sufism: Exploring spiritual networks and cultural resilience through a literature review - Md Ishak, Muhaizam; Omar , Ahmad Afiq Irshad; Fazial, Farahdina; Md. Noor, Mohamad Lukman Al Hakim (Journal of Islamic, Social, Economics and Development, 2025)
This study examines the role of social tariqah (Sufi orders) in fostering cultural resilience and spiritual networks within Nusantara Sufism, addressing gaps in understanding how these traditions adapt to modernity and digitalization. Despite growing interest in Sufism’s socio-cultural influence, fragmented scholarship has limited holistic insights into its transnational connectivity, digital evolution, and community impacts. The study aims to map spiritual networks, analyse digital adaptation strategies, and evaluate socio-economic contributions of tariqah, employing a systematic literature review of 32 peer-reviewed sources from Scopus and other academic databases (2018–2024). Thematic analysis reveals that Nusantara Sufism sustains cultural resilience through hybrid practices blending Islamic mysticism with local traditions, such as Rumi-inspired sema dances in Aceh and digital zikir (remembrance) sessions via platforms like Instagram and Zoom. Transnational networks, exemplified by the Qadiriyah and Shattariyya orders, facilitate cross-border spiritual tourism and educational outreach, while digital tools like the “limitless zawiya” (virtual lodge) democratize access to Sufi teachings. Socio-economically, tariqah drive community welfare through festivals, poverty alleviation programs, and ethical education curricula. However, challenges persist, including uneven digital access, commercialization of rituals, and tensions between spiritual authenticity and modernization. Theoretically, the study challenges stereotypes of Sufi passivity, positioning tariqah as dynamic actors in global Islamic discourse. Practically, it advocates for integrating Sufi ethics into policymaking and education to counter extremism and promote sustainable development. Limitations include a focus on Indonesia and potential underrepresentation of marginalized voices. Future research should explore digital Sufism’s long-term impacts, comparative studies across regions, and intersections of gender and spirituality within tariqah networks.